Digital based Madrasas: The Strategy to Improve the Quality of Madrasah Ibtidaiyah Performance - Hasan Baharun; Almakkiyatul Mukarramah (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
Abstract This study aims to analyze the internal and external factors that contribute to improving the quality of Islamic elementary schools’ performance in Probolinggo Regency, East Java, Indonesia. This is field research using the descriptive analysis method. Data was obtained from observation, interviews, and documentation. The collected data was processed and analyzed through the IE, IFE, and EFE matrices. The results of this study indicate that the internal factors of three Madrasah Ibtidaiyah are powerful and can overcome their weaknesses in improving the quality of digital-based madrasa performance. In addition, the three Madrasah Ibtidaiyah have relatively high opportunities to overcome challenges and is very responsive in improving the quality of digital-based madrasa performance. Furthermore, alternative strategies are formulated through SWOT analysis to improve the performance quality of digital-based madrasah by implementing intensive strategies through market penetration and product development. Madrasah Ibtidaiyah can penetrate the market more proactively using the IDN Network PortDi (Digital Portal) in carrying out digital-based madrasa performance. The research also suggests that the product development (madrasa’s administration and finance) can increase the professionalism of education staff in digital-based madrasah performance.Keywords: digital madrasa, performance, SWOT, internal and external analysis.AbstrakPenelitian ini bertujuan untuk menganalisis faktor-faktor internal dan eksternal yang berkontribusi terhadap peningkatan mutu kinerja Madrasah Ibtidaiyah di Kabupaten Probolinggo, Jawa Timur, Indonesia. Penelitian ini merupakan penelitian lapangan dengan menggunakan metode deskriptif analisis. Data diperoleh dari observasi, wawancara, dan dokumentasi. Data yang terkumpul diolah dan dianalisis melalui matriks IE, IFE, dan EFE. Hasil penelitian ini menunjukkan bahwa kemampuan faktor internal dari ketiga Madrasah Ibtidaiyah sangat kuat dan dapat mengatasi kelemahannya dalam meningkatkan kualitas kinerja madrasah berbasis digital. Selain itu, Madrasah Ibtidaiyah tersebut memiliki peluang yang cukup tinggi untuk mengatasi tantangan dan sangat tanggap dalam mengatasi tantangan dalam meningkatkan kualitas kinerja madrasah berbasis digital. Selanjutnya, alternatif strategi dirumuskan melalui analisis SWOT untuk meningkatkan kualitas kinerja madrasah berbasis digital dengan menerapkan strategi intensif melalui penetrasi pasar dan pengembangan produk. Madrasah Ibtidaiyah tersebut dapat melakukan penetrasi pasar dengan lebih proaktif menggunakan PorDi (Portal Digital) Jaringan IDN dalam melaksanakan kinerja madrasah ibtidaiyah berbasis digital. Pengembangan produk (administrasi madrasah, keuangan madrasah) dapat meningkatkan profesionalitas tenaga kependidikan dalam kinerja madrasah berbasis digital.Kata kunci: madrasah digital, kinerja, SWOT, analisis internal dan eksternal.